Peran Kepemimpinan Kepala Sekolah dalam Membangun Budaya Sekolah yang Positif (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Principal leadership plays a crucial role in building a positive school culture and improving the quality of education. The principal functions not only as a school administrative manager but also as an educational leader capable of optimally coordinating, mobilizing, and empowering all school resources. A positive school culture serves as the foundation for creating a conducive learning climate, improving teacher performance, and shaping the overall character of students. This study employed a qualitative approach with a literature review. Data were obtained from various scientific sources, including books, journals, and documents relevant to the topic of principal leadership and school culture. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing to gain a comprehensive understanding of the role of principal leadership in building a positive school culture. The study results indicate that effective principal leadership, characterized by a clear vision and mission, leadership competency, and the ability to build commitment and synergy among all school members, significantly influences the creation of a conducive school culture. A positive school culture impacts more innovative and contextual learning, strengthening extracurricular activities according to students' talents and interests, and developing student character traits such as religiosity, honesty, discipline, environmental awareness, creativity, independence, and national spirit. Therefore, effective principal leadership is the key to creating a quality and character-based school.